2021
DOI: 10.3991/ijoe.v17i06.22485
|View full text |Cite
|
Sign up to set email alerts
|

MostaLab: Performance Evaluation of Simultaneous Access in Analog Remote Laboratories

Abstract: A service oriented architecture for simultaneous access in the field of remote labs has been proposed and validated using stress load testing. The innovation of this work lies on the use of the parameters collected for the typical student and tested with the Artillery.io tool. Then, we have evaluated the performance of the laboratory by defining 5s the maximum waiting time that a request cannot be exceeded. This article also describes a use case showing how this architecture was designed and developed with 109… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Consequently, the author fully implemented the proposed remote laboratory activity using the assignment assessment pattern indicated in Figure 2. There are different detection CSPDarknet53 [15]. The updated Dense Net algorithm serves as the core of the convolution architecture.…”
Section: Proposed Autonomous Assessment System (Aas)mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the author fully implemented the proposed remote laboratory activity using the assignment assessment pattern indicated in Figure 2. There are different detection CSPDarknet53 [15]. The updated Dense Net algorithm serves as the core of the convolution architecture.…”
Section: Proposed Autonomous Assessment System (Aas)mentioning
confidence: 99%
“…Based on the results, we concluded that YOLO V5 outperforms YOLO V4. YOLOv4 in the Darknet is a modified version of YOLOv3 that leverages CSP Net, generating a new feature extractor backbone named CSPDarknet53 [15]. The updated Dense Net algorithm serves as the core of the convolution architecture.…”
Section: Proposed Autonomous Assessment System (Aas)mentioning
confidence: 99%